Mature cystic teratoma of the posterior fossa – A case report to enrich our data on the subject - Tzubery, Sappir; Hadelsberg, Uri P.; Ben-David, Eliel; Winestone, John S.; Cohen, Jose E.; Margalit, Nevo; Rajz, Gustavo (Interdisciplinary neurosurgery : Advanced techniques and case management, 2021)
Posterior fossa cystic lesions display a diagnostic challenge as the apparent simplistic image portrays a vast array of pathological entities. We hereby present the case of mature cystic teratoma of the posterior fossa with atypical radiological appearance, in a previously healthy 6-month old male, presenting with increased head circumferences, non-communicating hydrocephalus. The lesion underwent en bloc resection, and the infant was discharged home a week later with no neurological deficits. Follow-up MRI did not demonstrate any evidence of recurrence or residual tumor.